ION CHANNELS IN A CONTEXT OF THE DEVELOPMENT OF NEW MOLECULAR TARGETS FOR REGULATION OF UTERINE CONTRACTIONS - TARARINA, V.; SUKHA, I.; LAVRYK, R.; ARTEMENKO, O.; MOROZ, O. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Many women now have complications in childbirth due to poor labor, which often threatens both mother and fetus. Also,the problem of prevention and treatment of premature uterine contractions is unresolved. Therefore, in this work we investigated the influence of ion channels as the end stage effectors of the regulatory cascades in the contractility of myometrium. To better understand the participation of TRPC4, TRPV4 and BKCa ion channels in myometrial contractility, we conducted experiments, keeping in mind the fact that changes in ionic conductivity of the plasma membrane regulate spontaneous and agonist-induced contractions. On the myometrial preparations of pregnant rats usingisolated tissue tensiometry, the amplitude of contractile force was recorded under the activation of these ion channels by their selective agonists. Obtained results allow us to consider (-) – englerin A as a way to stimulate uterine contractions in case of insufficient response to oxytocin, because at a concentration of 1 nM a significant increase in contraction force was developed and did not differ statistically from the response to oxytocin or carbacholin. The use of an agonist at concentrations of 30-100 nM causes some suppression of contractility. Based on the results describing the role of TRPV4 channels, namely the reduction of uterine smooth muscle contractions in response to their selective agonist GSK1016790A administration, we suggest that the main effect of activation of these channels depends on the expression and activity of adjacent calcium-dependent potassium channels. Our experiments found that the use of the liposomal form of quercetin to activate BKCa channels inhibits the excitability of myometrial cells more effectively than that dissolved in DMSO, which is promising for the correction of premature or excessive uterine activity.